Analisis Media Sosial Facebook Dalam Menyiarkan Kegiatan Gerejawi di GMIM Baitani Paslaten Pada Masa Pandemi Covid-19 Tahun 2020 - Sonia Christy Pepah; Richard Gordon Mayopu (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
The Digital Era is a situation where technology provides convenience for the Global community, especially during the Covid-19 pandemic. Thus, happened to the GMIM Baitani Paslaten congregation, where the use of social media, especially Facebook, became a medium that provided convenience in carrying out worship services. This research uses Two-Step Flow Communication Theory according to Paul Lazarsfeld's models. This research explains how the analysis of Social Media, specifically Facebook, broadcasts ecclesiastical activities at GMIM Baitani Paslaten during the 2020 Covid-19 pandemic. GMIM Baitani Paslaten uses Facebook features such as live streaming as an alternative for congregations in carrying out ecclesiastical services. This study uses a qualitative analysis approach with explanatory descriptive writing methods and uses primary and secondary data sources. The results and conclusions of this study are The use of Facebook in church services during the Covid-19 pandemic, The use of Facebook during the pandemic, The impact of live streaming which Consists of attendance screening, Network connections, Broad coverage, Freedom of expression for the congregation, and Analysis of the occurrence of two step flow communication theory on the implementation of ecclesiastical activities. In this case, it is analyzed from the response of the GMIM Baitani Paslaten congregation when worshiping online using social media Facebook.